Elevated Serum Homocysteine Levels Have Differential Gender-Specific Associations with Motor and Cognitive States in Parkinson’s Disease - Megan C. Bakeberg; Alexa Jefferson; Maddeson Riley; Michelle Byrnes; Soumya Ghosh; Frank L. Mastaglia; Malcom K. Horne; Sarah McGregor; Rick Stell; Jade Kenna; Sue Walters; Dana Hince; et al. (Parkinson's Disease)
Background. Studies attempting to elucidate an association between homocysteine and symptom progression in Parkinson’s disease (PD) have had largely discrepant findings. This study aimed to investigate elevated serum homocysteine levels and symptom progression in a cohort of PD patients. Methods. Serum homocysteine, folate, and vitamin B12 levels were measured in 205 people with PD and 78 age-matched healthy controls. People with Parkinson’s disease underwent a battery of clinical assessments to evaluate symptom severity, including motor (MDS-UPDRS) and cognitive (ACE-R) assessments. Multivariate generalised linear models were created, controlling for confounding variables, and were used to determine whether serum markers are associated with various symptom outcome measures. Results. People with Parkinson’s disease displayed significantly elevated homocysteine levels (p<0.001), but not folate or vitamin B12 levels, when compared to healthy controls. A significant positive correlation between homocysteine and MDS-UPDRS III score was identified in males with Parkinson’s disease (rs = 0.319, p<0.001), but not in females, whereas a significant negative correlation between homocysteine levels and total ACE-R score was observed in females with Parkinson’s disease (rs = −0.449, p<0.001), but not in males. Multivariate general linear models confirmed that homocysteine was significantly predictive of MDS-UPDRS III score in male patients (p=0.004) and predictive of total ACE-R score in female patients (p=0.021). Conclusion. Elevated serum homocysteine levels are associated with a greater motor impairment in males with Parkinson’s disease and poorer cognitive performance in females with Parkinson’s disease. Our gender-specific findings may help to explain previous discrepancies in the literature surrounding the utility of homocysteine as a biomarker in PD.